KOMPARASI MODEL NUMERIK DAN FISIK PADA BANGUNAN PELIMPAH ALIRAN BEBAS DAN TERKONTROL : STUDI KASUS: BENDUNGAN LEUWIKERIS - Gerald Guntur Pandapotan Siregar; Budi Prasetyo; R. Alfin Septya Nugroho (Universitas Kristen Maranatha, 2022)
The number of variables needed in the hydraulic structure design process is very difficult if all parameters are defined mathematically. Numerical model is one alternative that has been widely used by experts in solving these difficulties. This study was conducted to determine the ability of the numerical model implemented on the spillway structure of the Leuwikeris Dam to approach the physical model that had previously been carried out. Numerical simulations were performed using Open Foam software as a Computational Fluid Dynamics (CFD) tool. Simulations were carried out in three scenarios, namely on QPMF, Q1000, and Q100 discharge flows. Each scenario will review the water pressure force acting on the launch channel wall and the energy attenuation performance of the stilling basin. The results of the study show that the water elevation upstream of the spillway at the QPMF, Q1000, and Q100 discharge flows is in accordance with the results of the physical modeling that has been carried out. The water level elevation on the wall opposite the spillway and sluice gate needs to exceed the existing wall elevation for QPMF. If runoff during QPMF is not permitted, then the elevation of the top of the wall needs to be increased to an elevation of +155.00 m. The stilling basin has not been able to reduce the flow at the planned Q100 year discharge, so it is necessary to modify the existing design.